Overview of the Australian national electricity market transmission use of system charges for integrating renewable generation to existing grid - Radzi, Nur Hanis
The Australian government has introduced the expanded renewable energy target scheme that aims to ensure that 20% of Australia%s electricity supply is generated from renewable sources by 2020. Hence, this will drive large changes and have direct effects on behaviour and investment in Australia%s market environment especially transmission use of system (TUoS) charges scheme. Therefore this study is intended to explore the TUoS charges in the Australian national electricity market (NEM) to the development of renewable generation. There are three issues that are focused in this paper: (i) the transmission configurations for connecting the remote generation cluster to the existing grid; (ii) the Australian NEM TUoS charges; and (iii) the Australian energy market operator policy on the allocation of the cost of providing shared transmission services to different parties for new and existing terminal stations. The 59-bus system of the South East Australian power system is used for the case study in order to verify the concepts and determine the efficient and economic way to connect a new renewable generation to the existing grid.